Substituted Judgement: Should Life-Support Decisions be Made by a Surrogate? - Príncipe-Rodríguez, Karem; Rodríguez-Cintrón, William; Torres-Palacios, Alfonso; Casal-Hidalgo, Jesús (Puerto Rico Health Sciences Journal, 2014)
see manuscript